Provisions of the Australian Human Rights Commission Legislation Bill 2003 - Australia. Parliament. Senate. Legal and Constitutional Legislation Committee; Payne, Marise Ann, 1964- (Canberra : The Committee, 2003)
Report and dissenting report include discussion and recommendations on proposals to change structure of Human Rights Commission including replacement of five specialist Commissioners, who include Race Discrimination Commissioner and Aboriginal and Torres Strait Islander Social Justice Commissioner, with three generalist Commissioners; Commission's right to intervene in court proceedings and role of Attorney-General.
"May 2003".
Chair: Senator M Payne.
Also available in an electronic version on the Internet. Address as of 10 July 03: http://www.aph.gov.au/senate/committee/legcon_ctte/human03/report/report.pdf
Adobe Acrobat Reader is required to view or print the PDF files.
Keywords: Australia. -- Parliament. -- Senate; Human rights -- Australia; Law - Administrative law - Commonwealth; Australia